2(x-10)+(x-10)=46

Simple and best practice solution for 2(x-10)+(x-10)=46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-10)+(x-10)=46 equation:


Simplifying
2(x + -10) + (x + -10) = 46

Reorder the terms:
2(-10 + x) + (x + -10) = 46
(-10 * 2 + x * 2) + (x + -10) = 46
(-20 + 2x) + (x + -10) = 46

Reorder the terms:
-20 + 2x + (-10 + x) = 46

Remove parenthesis around (-10 + x)
-20 + 2x + -10 + x = 46

Reorder the terms:
-20 + -10 + 2x + x = 46

Combine like terms: -20 + -10 = -30
-30 + 2x + x = 46

Combine like terms: 2x + x = 3x
-30 + 3x = 46

Solving
-30 + 3x = 46

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + 3x = 46 + 30

Combine like terms: -30 + 30 = 0
0 + 3x = 46 + 30
3x = 46 + 30

Combine like terms: 46 + 30 = 76
3x = 76

Divide each side by '3'.
x = 25.33333333

Simplifying
x = 25.33333333

See similar equations:

| 2(6x+2)=0 | | x^2+84-520=0 | | (3x-1)(2x+1)=0 | | x=1287.4(2017)+48470 | | 10(s-4)=-146 | | =31x-18y | | (2x^2-3x^3)-(9x^2-5x^3)=0 | | 100000=1287.4x+48470 | | (2x^2-3x^3)(9x^2-5x^3)=0 | | 22-3x=2 | | 18-2(5-3x)=-5x-3 | | (2x^2-3x^3)(9x^2-5x^3)= | | 4(d-8)+3= | | (4x-13y)-(-27x+5y)= | | 3(x+4)+3=-5(x-8)-1 | | 6(t+4)=-6 | | 7(r+9)= | | 10-48x-12=27x+36x | | 6w-w+5w= | | (16-10)x-35000=0 | | 5x(3-13)=100 | | 7(3s+10)=238 | | 10x+8=4x+3 | | 2(2l+2)=24 | | 8x-32=5+10x | | -3(2t+9)=-57 | | (2y+2)*350=(0.6y+6)*350 | | 8x^3-30x^2+48=0 | | 2a+9=8a-9 | | 4(a-4)=16 | | 5(f-3)=-35 | | 10(s-3)=-58 |

Equations solver categories